2000
DOI: 10.1046/j.1537-2995.2000.40080931.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion‐related sepsis due to Serratia liquefaciens in the United States

Abstract: S. liquefaciens is an increasingly recognized cause of transfusion-related sepsis and is associated with a high mortality rate. S. liquefaciens can contaminate both RBCs and platelets, but the mechanism(s) of contamination remain unknown. Increased attention to pretransfusion visual inspection may avert the transfusion of some S. liquefaciens-contaminated RBC units. However, more sensitive rapid diagnostic tests are needed to further reduce the risk of transfusion-related sepsis and endotoxic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 17 publications
2
50
0
Order By: Relevance
“…Category IB 3. Complete infusions of blood or other blood products within 4 hours of hanging the blood [231][232][233][234]. Category II 4.…”
Section: Category Ib II Surveillancementioning
confidence: 99%
“…Category IB 3. Complete infusions of blood or other blood products within 4 hours of hanging the blood [231][232][233][234]. Category II 4.…”
Section: Category Ib II Surveillancementioning
confidence: 99%
“…Serratia is also a Gram-negative bacterium, which proliferates easily in poor environment at +4 -+22 o C. The bacteria were isolated from both red blood cell concentrates and platelets concentrates. Transmitting Serratia, especially Serratia liquefaciens, causes transfusionassociate sepsis, most often fatal (1,20). A prospective analysis of bacterial cultures from whole blood and red blood cell concentrates has shown that bacterial contamination is much more common in blood components, i.e.…”
Section: Bacterial Infections Transmitted With Red Blood Cell Concentmentioning
confidence: 99%
“…Although rare, bacterial contamination of stored autologous units can rarely cause sepsis and death (Dodd 1992;Roth 2000) and is also subject to all the potential clerical/procedural errors as allogeneic blood albeit avoiding the hazards of TTIs and immunological hazards associated with allogeneic transfusion. It also requires a weekly commitment from the patient and involves a weekly appointment at the donation site, in addition to staffing, other practical issues and related costs of the PABD programme.…”
Section: Preoperative Autologous Blood Donation (Pabd)mentioning
confidence: 99%